2015
DOI: 10.1016/j.contraception.2015.03.013
|View full text |Cite
|
Sign up to set email alerts
|

The acceptability of contraception task-sharing among pharmacists in Canada — the ACT-Pharm study

Abstract: Pharmacies from all areas throughout BC, responded and report a high degree of acceptability and feasibility for independent prescription of hormonal contraceptives. As pharmacists are often the most accessible health professional in rural areas, pharmacist provision of hormonal contraceptives has potential to improve access to contraception.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 20 publications
0
32
0
1
Order By: Relevance
“…Any disagreements were resolved after discussion. Of the studies, six were from the United States, five from Australia, three from Canada, two from the UK (England and Scotland) and one from South Africa . Across the publications, there were specific and varying definitions of ‘rural’, ranging from the number of people within a geographic area to more complex approaches, which included the number and nature of other health services within a geographic area or relatively close by (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Any disagreements were resolved after discussion. Of the studies, six were from the United States, five from Australia, three from Canada, two from the UK (England and Scotland) and one from South Africa . Across the publications, there were specific and varying definitions of ‘rural’, ranging from the number of people within a geographic area to more complex approaches, which included the number and nature of other health services within a geographic area or relatively close by (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Survey questions were drafted after a review of the existing literature on pharmacist prescription of contraception [35]. Our survey builds off of previous work that explored Canadian and American pharmacists interests in prescribing HC [4,5]. The survey was administered in fall 2015, subsequent to the legislation passing in Oregon but prior to implementation of the policy or to wide-spread education of pharmacists detailing the guidelines for participation.…”
Section: Methodsmentioning
confidence: 99%
“…Age, sex and years since pharmacy degree were recorded as categorical variables. Pharmacy type was categorized as: department-mass merchandise, chain, independent, hospital or other [4]. For pharmacy position, respondents were asked to check all that applied (full-time, part-time, floater, pharmacy manager, hospital pharmacist, other).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacist's consultation fees as well as inappropriate refusal to provide OC might also add an extra burden. If OC are OTC, pharmacists will have to provide adequate counseling about pill use; a study of pharmacists in Canada indicated that was acceptable and feasible for them [40].…”
Section: Oral Contraceptives Over the Counter (Otc)mentioning
confidence: 99%